Absorption spectra of ternary complexes of rare earths - Tandon, S. P.; Bhutra, M. P.; Gupta, Anup (Rev. Téc. Fac. Ing. Univ. Zulia)
The absorption spectra of ternary complexes of Pr3+ and Nd 3+ in different environments i.e. water, methanol, formamide and DMSQ (dimethyl-sulphoxide) been recorded in the visible region, using methionine as primary ligand and propane -1,2-diol as secondary ligand. The energies and intensities of various transitions calculated using the Judd-Ofelt relations are in good agreement with these obtained experimentally. This study reveals that the complexes are covalent in nature.